TEACHERS’ ATTITUDE TOWARDS OCCUPATIONAL PRESTIGE - Paulauskas, Rolandas; Bakutytė, Rima; Ušeckienė, Lidija (Acta Paedagogica Vilnensia, 2010)
The study examines the way Lithuanian educators view different factors that determine occupational prestige. The questionnaire utilized by the authors focuses on the assessment of three perspectives: factors that currently effect occupational prestige; evaluation of the factors that should determine occupational prestige; and assessment of personally important occupational factors to the teachers. The study took place in 2009 and included a random sample of 114 teachers of different ages, who worked in different educational facilities and locations. Research methods included literature review, data collection survey as well as quantitative data analysis. The study found that all the factors related to the prestige of the profession could be divided into three groups: 1) occupation’s value to the society cluster; 2) career advancement and socioeconomic rewards cluster; and 3) opportunities for professional growth and development cluster. According to the respondents, the most significant determinants of occupational prestige are socioeconomic rewards and career advancement opportunities that are followed by professional growth and development factors. In contrast to public perception prevailing in some other European countries, Lithuanian teachers do not consider worthiness of their work to the society to be of great importance. As far as occupational prestige is concerned, age, years of employment, level of education, type of educational facility or location of residence in most cases had no significant effect upon the opinion of the respondents.